An Investigation into the Effect of Matching Exercises on the 10th form Students’ Vocabulary Improvements at Dinh Tien Hoang High School in Ninh Binh City - Lê, Thị Việt Hà (ĐHNN, 2017)
This research was conducted to investigate the effect of matching exercises on grade 10 students’ vocabulary improvements. Two grade 10th classes majoring in natural sciences were selected and divided into control and experimental groups. This is a quasi-experimental study which aimed at establishing the positive impacts of matching exercises on students’ vocabulary improvements in comparison with the conventional teaching and learning of vocabulary at most high schools in Ninh Binh at present. In this experimental study, 43 grade 10 students applied matching exercises for a period of 4 months in school year 2014-2015 while 43 other students belonging to the control group followed the conventional teaching and learning. The subjects’ vocabulary gains were measured by a vocabulary test on lexical aspects such as word meaning, vocabulary recognition and production in different contexts. Both pretest and posttest were administered in chronologic order, before and after the experimental program. T-test which was employed to make a comparison between pretest and posttest scores gained by two groups demonstrated that the experimental group had made more improvements in the English vocabulary than the control group. Moreover, the participants’ responses to the questionnaire also showed that most students who used matching exercises regularly found them very effective. This result supported the empirical findings mentioned above and reemphasized the outstanding benefits of matching exercises to the learning and teaching L2 vocabulary at high schools in the future.